Clinical profile, risk factors and aetiology of young stroke: a tertiary care hospital based study from the Sub-Himalayan region in North India - Kapoor, Dhiraj; Dhiman, Ashish; Sharma, Rupinder; Sundar, Shyam (International Journal of Research in Medical Sciences, 2017)
Background: Rapid urbanisation of rural areas is predicted to increase the incidence of risk factors for vascular events like stroke. There is scarcity of literature addressing issue of stroke from Sub-Himalayan region in North India. Methods:The study was conducted in the department of medicine, R. P. govt. medical college, Kangra, Himachal Pradesh. Consecutive patients between the age of 15-45 years presenting with signs and symptoms of stroke in a duration of one year were included in the study. CT scan-head and lipid profile was done in all patients. Other relevant investigations to rule out aetiology were undertaken. Results: Thirty two patients with the mean age of 41.1 ± 5.41 years were recruited. The incidence of stroke in young forming 8.55% of the total stroke patients (374). There were larger proportion of male patients with a ratio of 3:1.16 patients (50%) presented between 6 am and 12 pm in the morning hours of day. Maximum patients presented in winter months from November to January. Average delay of presentation to hospital was 30.8 hours. 19 patients (59.3%) presented with infarct. Most common symptom reported was weakness in 18 (56.2%). Predominant traditional risk factors observed was hypertension in 18 (53.1%). Hyperhomocysteinemia was seen in 4 patients (12.5%). Primary antiphospholipid antibody syndrome was seen in 2 (6.25%). Conclusion:This study demonstrated predominant presence of conventional risk factors in young strokes. There was substantial time delay of presentation. Majority of patients presented in winter months. Prevention of vascular risk factors as well as issue of factors leading to delay in presentation needs to be addressed.